Can role models and skills training increase women’s voice in asset selection? Experimental evidence from Odisha, India - Kosec, Katrina; Kyle, Jordan; Narayanan, Sudha; Raghunathan, Kalyani; Ray, Soumyajit (International Food Policy Research Institute, 2024)
We explore the impacts of exposing women to female role models and providing skills training on outcomes related to women’s aspirations and engagement in demanding assets under India’s Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA)—the largest public works program in the world, which solicits citizen input on which assets to build and where. While the role model treatment exposes women to a video with stories of female role models from neighboring districts who successfully demanded assets, the skills training shows women how to identify individual and group needs for assets, frame their demands, and articulate them to public functionaries. In a randomized controlled trial spanning 94 villages and involving approximately 2,600 women, we find that exposure to role models alone has limited impacts, but when combined with skills training, there are strong positive impacts on women’s aspirations and engagement in demanding assets. This reveals that even a light-touch training can significantly benefit women’s voice and agency in village decision-making.